Vaginal health in breast cancer survivors: a practical clinical approach - Maya Ram-Weiner; Shani Paluch-Shimon; Tanir M. Allweis; Ahinoam Lev-Sagie (Therapeutic Advances in Medical Oncology)
Thanks to advanced treatments, many breast cancer (BC) patients become long-term survivors, yet suffer a diminished quality of life (QOL) due to estrogen deprivation. This affects adherence to endocrine treatments, potentially compromising outcomes. While there is increasing recognition of genitourinary side effects, vulvovaginal health remains under-addressed. Many clinicians overlook the impact of endocrine therapy on the genitourinary system and lack knowledge about safe and effective treatments, leading to undertreatment and aggravated symptoms. Proper treatments not only boost the QOL but also enhance endocrine therapy adherence, directly influencing long-term outcomes. We offer an updated review and guidelines on vulvovaginal health for BC survivors. Our review details the genitourinary hypoestrogenic state, its effects on the genitourinary system, its diagnosis, as well as the safety, effectiveness, and available treatment options for BC patients. Furthermore, we offer practical recommendations for managing vulvovaginal symptoms, considering underlying mechanisms and the safe use of topical estrogen, with attention to receptor and cancer status.